De l’élève et de l’enseignant en institut médico-professionnel : un éclairage pour toute relation d’enseignement et une interrogation de la déficience intellectuelle: Pupils and teachers in educational centers for backward adolescents (Instituts médicoprofesionnels): thoughts on the teaching relationship and some queries about mental deficiency - Simon, Marie-Agnès (Revue francophone de la déficience intellectuelle, 1998)
L’analyse d’entretiens d’instituteurs spécialisés en Instituts Médico-Professionnels offre un repérage de la place qu’occupe l’élève dans la relation d’enseignement. Ainsi peut être définie une «position» de ces enseignants qui prendrait en compte les mécanismes d’identification et de défense en jeu dans toute relation. Trois formes ont pu être mises à jour, parfois combinées chez un même enseignant ; une position dite «en brisure» c’est-à-dire en restriction-diminution de sa capacité enseignante par identification de l’enseignant à l’élève dit déficient, une position en délinquance par identification de la tâche de l’enseignant à celle des éducateurs et une position acculturante du fait d’une assise culturelle (trajet universitaire) et d’une formation de base qualifiante. Cette recherche donne des outils pour questionner toute relation d’enseignement et le marquage «déficience intellectuelle» sur l’élève et l’enseignant. Abstract Analysis of interviews with specialist teachers working in educational centres for backward adolescents helps us to pinpoint the situation of a given pupil in the teaching relationship. On the basis of such an investigation we can ascribe to each of the teachers concerned a «position» arising from the identification and defence mechanisms involved in all relationships. Three forms of this position have emerged, though sometimes all three are to be found combined in one teacher. One position is described as «en brisure», a heraldic term meaning «fractured» and reflecting a narrowing and fragmentation of the teacher’s effectiveness because of his or her identification with a pupil labelled as defective. Another instance of an unsactisfactory position is that where the teacher fails through confusing his or her fundamentally educationel tasks with the socializing activities of other members of staff. A third and this time a positive position is found in teachers capable of bringing about some true cultural integration in their pupils, thanks to an adequate basic training and suitable cultural background, perhaps including university studies. Research of this kind enables us to scrutinize all kinds of teaching relationships and the extent to wich either pupil or teacher may be influenced by the notion of «mental retardation».